The influence of personality factors on attitudes towards counterfeiting of luxury brands and purchase intention - Teah, Min; Phau, Ian (University of Western Sydney, 2008)
This paper examines how personality factors influence attitudes towards counterfeiting of luxury brands and purchase intention. Attitudes towards counterfeiting of luxury brands is found to influence purchase intention. A factor analysis of the scale "attitudes towards counterfeiting of luxury brands" revealed two factors, which are "perceptions of counterfeits" and "social consequences". Status consumption and integrity are strong influencers of purchase intention, whereas personal gratification, value consciousness, and novelty seeking had weaker influencing relationships. The research findings can be used to formulate strategies to better counter counterfeiting.